Enzyme-mediated ligation methods - Nuijens, Timo 1981-; Schmidt, Marcel ca. 20./21. Jh (Methods in Molecular Biology, 2019)
This volume discusses different enzyme-catalyzed ligation methodologies for a variety of different chemical transformations. This book wants readers to view enzymes as a powerful tool in both academic and industrial research. Chapters in this book cover topics such as sortase A-mediated generation of site-specifically conjugated antibody-drug conjugates; omniligase-catalyzed inter- and intramolecular ligation; ligation catalyzed by microbial transglutaminase; peptide cyclization mediated by cyanobactin macrocyclases, butelase 1 and sortase A; using BioID as a tool for protein proximity labeling in living cells; and inducible, selective labeling of proteins via enzymatic oxidation of tyrosine. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Cutting-edge and thorough, Enzyme-Mediated Ligation Methods is a valuable resource for students and scientists from different disciplines who are interested in using enzymatic strategies to answer their research questions.